Vagus nerve stimulation in chronic refractory epilepsy: chasing the cardiologist - Chaudhary, Ansh; Chaudhary, Bhupendra (International Journal of Advances in Medicine, 2021)
Epilepsy the second most common chronic neurological disorder after stroke affect 0.5-2% population worldwide. Antiepileptic drugs though remain the corner stone in management of epilepsy in majority of patients but still 30% of patients continues to have seizure or experience unacceptable pharmacological side effect. Electrical stimulation of vagus nerve is an effective and promising neurophysiological treatment for patients with refractory epilepsy who are either unsuitable candidate of surgery or falls in category of surgically refractory epilepsy.